Sistema de vivienda progresiva y resiliente para la localidad de Sumapaz – Bogotá (2022)
The rapid growth of cities and their industrialized development in recent decades have generated the ideal of the city as the main factor of economic and social well-being, something somewhat logical considering the economic opportunities that it can offer its inhabitants. phenomenon that sponsors and directs the highest percentage of state investment in urban areas, on the other hand there is also the other side of reality, the rural areas of the cities, of cities that like Bogotá have the privilege of having extensive rural areas within its own district and that reach up to triple the same urban area, however the rural territory, even with such a considerable proportion of land, seems to be almost imperceptible to the state gaze and especially in terms of investment and resources, ignoring the great potential that it can offer in environmental services, ecosystems, food security and among others.